GAMIFYING HR SYSTEMS TO BOOST EMPLOYEE ENGAGEMENT: A USER-CENTERED DESIGN CASE STUDYOctarivinski - Vyoni Reviolencia Octarivinski; Wawan Dhewanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
Employee engagement is a critical driver of organizational success, yet many Human Resource Information Systems (HRIS) are still perceived as transactional tools, with employees showing limited voluntary use beyond mandatory functions. This study examines SF HRIS (pseudonym), where underutilization of interactive features was identified as a user experience (UX) gap. To address this challenge, the study applied Design Thinking as the research design, guiding a structured process of Empathize, Define, Ideate, Prototype, and Test. Through a qualitative case study involving five participants across three user personas, the research identified key pain points such as lack of recognition, minimal incentives, and flat interaction design. Based on these insights, gamification was proposed as a UX strategy to enhance engagement. A prototype was developed with elements including points, leaderboards, achievements, and rewards. Feedback was collected through semi-structured interviews and analyzed thematically, with responses categorized using TAM constructs (Perceived Usefulness, Perceived Ease of Use, Behavioral Intention) as qualitative interpretive lenses. Findings suggested that participants perceived the gamified features as useful, intuitive, and motivating, highlighting improvements in interaction, navigation, and alignment with personal and team goals. The study concludes that gamification can effectively address UX gaps in HRIS by transforming systems from transactional tools into engaging employee experience platforms. Methodologically, the research demonstrates how Design Thinking and qualitatively adapted TAM constructs can be combined to support user-centered innovation in HR technology.